Development of a conceptual model of product emotion in the pre-purchase context - Seva, Rosemary R. (Animo Repository, 2005)
A conceptual model of product emotion was developed considering the pre-purchase context. The main proposition of this model is that affect generated in the pre-purchase context is a result of product evaluation using consumer-generated criteria. The process starts when a consumer becomes interested in the distinctive, integrative and interactive features of a product. A survey was conducted to determine the criteria used by consumers when buying clothes, watches, and electronic products. A total of 34 criteria were identified in the process. These 34 criteria were personality, aesthetics, design/fitting, function, brand, durability, quality features, material and expected life. Affect is the pre-purchase context was determined by conducting a field survey where consumers, were asked about the emotions they experienced before purchasing. Pre-purchase affect is dominated by positive feelings. Only 5 emotions can be classified as negative while the rest indicate cheerfulness, enthusiasm and hopefullness. The result of the multidimensional scaling showed that pre-purchase affect has several dimensions.